ANALISIS KEPUASAN DAN KEBUTUHAN PENGGUNA LULUSAN INSTITUT TEKNOLOGI KALIMANTAN DENGAN MENGGUNAKAN METODE RATING SCALE - Ridhwan Haliq (Program Pendidikan Vokasi Universitas Indonesia, 2020)
In the world of work, the quality of employees is very concerned about supporting smooth work. Companies definitely choose prospective employees who have the qualities that the company expects. because of this, universities are required to develop soft skills that are balanced with hard skills. In addition to the quality of graduates, universities must also know the needs of companies and adjust to DUDI (world of work and industry). This will have an impact on graduates who will enter the world of work. The better the name of the college, the greater the opportunity for college graduates to join the company.Keywords: Quality of Graduates, Satisfaction, and Company Needs.